2023
DOI: 10.1200/jco.2023.41.16_suppl.3051
|View full text |Cite
|
Sign up to set email alerts
|

Detection of early-stage cancers using circulating orphan non-coding RNAs in blood.

Abstract: 3051 Background: Orphan non-coding RNAs (oncRNAs) are a novel category of small RNAs (smRNAs) that are present in tumors and largely absent in healthy tissue. We investigated the utility of oncRNAs extracted from serum for early cancer detection across seven cancer types. Methods: We collected 2,882 serum samples from individuals with known cancers of the bladder ( n=152), breast (220), colon and rectum (141), kidney (283), lung (281), pancreas (287), and stomach (280) as well as donors with no history of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We had previously observed that given the tissue-specific landscape of chromatin accessibility in different cancers, oncRNA expression patterns are unique to cancer types and subtypes , allowing us to detect tissue of origin among different cancer types non-invasively from blood (Karimzadeh et al, 2023a). We hypothesized that biological differences of lung adenocarcinoma and squamous cell carcinoma would also be reflected in cell-free oncRNA content, allowing us to distinguish these major subtypes of NSCLC.…”
Section: Orion Can Identify Tumor Subtype From Circulating Oncrnasmentioning
confidence: 99%
See 1 more Smart Citation
“…We had previously observed that given the tissue-specific landscape of chromatin accessibility in different cancers, oncRNA expression patterns are unique to cancer types and subtypes , allowing us to detect tissue of origin among different cancer types non-invasively from blood (Karimzadeh et al, 2023a). We hypothesized that biological differences of lung adenocarcinoma and squamous cell carcinoma would also be reflected in cell-free oncRNA content, allowing us to distinguish these major subtypes of NSCLC.…”
Section: Orion Can Identify Tumor Subtype From Circulating Oncrnasmentioning
confidence: 99%
“…OncRNAs are abundant, stable, and actively secreted from living cancer cells into the blood (Wang et al). We have generated a first-in-kind catalog of over 777,291 oncRNAs across major cancer types (Karimzadeh et al, 2023a). Some oncRNAs, such as T3p, exhibit pro-metastatic roles, while others could emerge as a byproduct of reprogrammed RNA metabolism.…”
Section: Introductionmentioning
confidence: 99%